Role of tourism in long term economic growth in Pakistan - Waliullah, Waliullah; Kakar, Mehmood Khan (2008)
Tourism activities are multi-pronged with mostly positive impact on any economy. This study attempts to investigate the role of tourism in the long run economic development in case of Pakistan. The tourism led growth hypothesis is confirmed through autoregressive distributed lag (ARDL) and vector error correction model econometric framework using a time series data for the years that span from 1975 to 2005. The study explores the potential contribution of tourism to economic growth and development. The combination of results pointed a stable long run relationship among tourism, exchange rate and economic expansion in the Pakistan economy. The results show that receipts from the tourism industry significantly contribute to the current level of gross domestic product and the economic growth of Pakistan economy both in short run and long run. Our findings imply that Pakistan could enhance its shortrun economic growth by strategically strengthening its tourism industries.